A three-dimensional analytical model and parameter determination method of the elastic vibration of a railway vehicle carbody. Issue 4 (2nd April 2020) - Akiyama, Yuki; Tomioka, Takahiro; Takigami, Tadao; Aida, Ken-ichiro; Kamada, Takayoshi
ABSTRACT: Reducing railway vehicles' three-dimensional (3D) elastic vibration is needed to improve passenger comfort. This paper presents a 3D analytical model and parameter determination method for the elastic vibration of a carbody. The carbody is modelled as a simple box-type structure consisting of an anisotropic 3D elastic body treated as a continuous system. This model can express complicated 3D elastic vibration (such as lateral–vertical coupled vibration) with fewer degrees of freedom and at a lower computational cost than the detailed finite element model. A model parameter determination method using particle swarm optimisation was also proposed. Application to a Shinkansen-type test vehicle showed good agreement between measured and calculated results with a maximum natural frequency differences of the targeted six elastic vibration modes within 0.86%, indicating the effectiveness of the proposed model and parameter determination method.